Best student paper award at the 2021 IEEE Madrid PowerTech conference - Aristidou, Petros (My University, 2026)
Our paper Microgrid Operational Optimisation with Dynamic Voltage Security Constraints received a best student paper award at the 2021 IEEE Madrid PowerTech conference.
Keywords: Sciences